Circulating ECV-Associated miRNAs as Potential Clinical Biomarkers in Early Stage HBV and HCV Induced Liver Fibrosis - Lambrecht, Joeri; Jan Poortmans, Pieter; Verhulst, Stefaan; Reynaert, Hendrik; Mannaerts, Inge; van Grunsven, Leo A. (Frontiers in Pharmacology, 2017)
Introduction: Chronic hepatitis B (HBV) and C (HCV) virus infection is associated with the activation of hepatic stellate cells (HSCs) toward a myofibroblastic phenotype, resulting in excessive deposition of extracellular matrix, the development of liver fibrosis, and its progression toward cirrhosis. The gold standard for the detection and staging of liver fibrosis remains the liver biopsy, which is, however, associated with some mild and severe drawbacks. Other non-invasive techniques evade these drawbacks, but lack inter-stage specificity and are unable to detect early stages of fibrosis. We investigated whether circulating vesicle-associated miRNAs can be used in the diagnosis and staging of liver fibrosis in HBV and HCV patients. Methods: Plasma samples were obtained from 14 healthy individuals and 39 early stage fibrotic patients (F0–F2) with chronic HBV or HCV infection who underwent transient elastography (Fibroscan). Extracellular vesicles were extracted from the plasma and the level of miRNA-122, -150, -192, -21, -200b, and -92a was analyzed by qRT-PCR in total plasma and circulating vesicles. Finally, these same miRNAs were also quantified in vesicles extracted from in vitro activating primary HSCs. Results: In total plasma samples, only miRNA-200b (HBV: p = 0.0384; HCV: p = 0.0069) and miRNA-122 (HBV: p < 0.0001; HCV: p = 0.0007) were significantly up-regulated during early fibrosis. In circulating vesicles, miRNA-192 (HBV: p < 0.0001; HCV: p < 0.0001), -200b (HBV: p < 0.0001; HCV: p < 0.0001), -92a (HBV: p < 0.0001; HCV: p < 0.0001), and -150 (HBV: p = 0.0016; HCV: p = 0.004) displayed a significant down-regulation in both HBV and HCV patients. MiRNA expression profiles in vesicles isolated from in vitro activating primary mouse HSCs resembled the miRNA expression profile in circulating vesicles. Conclusion: Our analysis revealed a distinct miRNA expression pattern in total plasma and its circulating vesicles. The expression profile of miRNAs in circulating vesicles of fibrotic patients suggests the potential use of these vesicle-associated miRNAs as markers for early stages of liver fibrosis.